The ASEAN Free Trade Agreement: Building bloc or stumbling bloc for multilateral trade liberalization? - Andreas Lendle (Graduate Institute of International Studies, 2007)
This paper investigates empirically whether the ASEAN Free Trade Agreement had a building bloc or stumbling bloc effect on subsequent changes in MFN tariffs of four major ASEAN members. The method resembles the one recently used by Nuno Lim\~ao. We use tariff data to test whether MFN tariffs were changed differently for preferential products compared to otherwise similar products without a preference. We find a significant building bloc effect for Indonesia, the Philippines and Thailand. MFN tariffs of preferential products were reduced by more than for non-preferential products. We obtain ambiguous effects for Malaysia. This suggests that overall the ASEAN Free Trade Agreement has rather helped than hindered nondiscriminatory trade liberalization.
Keywords: 330; Freihandelszone; Meistbegünstigung; Handelsregionalismus; Handelsliberalisierung; ASEAN-Staaten